The rhetoric of American exceptionalism critical essays - Edwards, Jason A., 1973-; Weiss, David (McFarland & Company, Inc., Publishers, 2011)
"This book of eleven critical essays explores the American exceptionalism as it is manifested across the American presidency, U.S. foreign policy, religion, economics, American history, television news, and mass-mediated sport. It demonstrates the importance of exceptionalism to the mythology, sense of place, direction, and identity of the United States, within and outside the realm of politics"--Provided by publisher.